PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA MELALUI STRATEGI PEMODELAN (MODELING) SISWA KELAS VIIIA SMP NEGERI 1 MANDAI KABUPATEN MAROS - NFN Aminah (Multilingual, 2015)
This study aims at investigate the improvement of process and learning achievement of writing news text through modeling strategy og grade VIIIA students at SMPN 1 Mandai in Maros district. This study is a classroom action research and was using a descriptive design. Data of the study was the implementation and learning achievement of writing news text through modeling strategy. The data were collected by conducting observation and test in writing news text. The procedure in implementing the study consisted of two cycles. Each cycle was conducted three times. The data then analyzed descriptively. The result of the study reveal that (1) the process in writing news text through modeling strategy was increased. Teacher’s activity during the cycle I shows 52,4% of descriptor application is in extremely good categoryas well as in the cycle II, 88,1% of descriptor application is in extremely good category. The students’ activity during cycle I is 15,4% is in active category and in cycle II, 89,7% is in active category. (2)The learning achievement of writing news textthrough modeling strategy was improved. The conclusion based on the result of the study is the learning achievement in writing news text through modeling strategy of grade VIIIA students at SMPN 1 Mandai was improved significantly. Therefore, it is suggested to teachers who have problems in conducting writing news text should apply modeling strategy. The strategy can overcome the problems in writing news text in class because students are able to construct the knowledge which refer to themodel.